Press and national movement in India, 1911-1947 - Sinha, Basanti (Delhi : Manak, 1994)
With special reference to Bihar, India.
Includes bibliographical references 263-268 and index.
Keywords: Press -- India -- History -- 20th century; Journalism -- India -- History -- 20th century; Nationalism -- India -- History -- 20th century; India -- Politics and government -- 20th century